Evaluation of Smoking Characteristics among Community-Recruited Daily Smokers with and without Posttraumatic Stress Disorder and Panic Psychopathology - Marshall, Erin C. (2008)
The present investigation compared 123 community-recruited daily smokers with posttraumatic stress disorder (PTSD), panic disorder (PD), nonclinical panic attacks (PA), or no current Axis I psychopathology (controls; C) in terms of nicotine dependence, smoking rate, quit history, severity of symptoms during past quit attempts, and motivation for and expectancies about smoking. No differences were observed between groups in regard to smoking rate or nicotine dependence. The PTSD group reported making more lifetime quit attempts than the other groups, and the PTSD and PD groups perceived more severe symptoms during past quit attempts. The PD and PTSD groups reported greater motivation to smoke to reduce negative affect. Individuals with PTSD endorsed a stronger expectation that smoking would alleviate negative mood states and would produce negative consequences. Overall, results suggest that smokers with PD or PTSD differ from other smoking groups in a number of clinically significant ways.